One-step electrodeposition of free-standing flexible conducting PEDOT derivative film and its electrochemical capacitive and thermoelectric performance. (10th January 2017) - Ye, Guo; Xu, Jingkun; Ma, Xiumei; Zhou, Qianjie; Li, Danqin; Zuo, Yinxiu; Lv, Liangjing; Zhou, Weiqiang; Duan, Xuemin
Graphical abstract: Highlights: A monomer based on two EDOT units bridged by the oxygen capped alkylene was prepared. The EDOT derivative was easily electrodeposited into free-standing PBEDTH paper. The cyclic life of PBEDTH paper with 0.11 S cm −1 was 86.7% after 5000 cycles. Abstract: Free-standing conductive films are important for the application in organic electronics. However, PEDOT as one of the most promising CPs is difficult to be prepared into free-standing paper. Herein, a novel EDOT derivative, 1, 6-bis((2, 3-dihydrothieno[3, 4- b ][1, 4]dioxin-2-yl)methoxy)hexane (BEDTH), was synthesized and easily electrodeposited into free-standing flexible conducting poly(1, 6-bis((2, 3-dihydrothieno[3, 4- b ][1, 4]dioxin-2-yl)methoxy)hexane) (PBEDTH) in CH2 Cl2 containing 0.1 M Bu4 NBF4 . The free-standing PBEDTH films with the conductivity of 0.11 S cm −1 were characterized by FT-IR, UV–vis, SEM, TG, dynamic mechanical analysis and electrochemical method, respectively. Electrochemical results indicated that the specific capacitance of PBEDTH film was 40.8 F g −1 at the current density of 0.5 A g −1 in ionic liquid BmimBF4 with the cycling capacitance retention of 86.7% after 5000 cycles. Additionally, the thermoelectric property of free-standing flexible PBEDTH film was also studied, showing the Seebeck coefficient was 37.2 μV K −1 and the power factor was 0.015 μW K −2  m −1 at 300 K. Although the capacitive and thermoelectric performance is not satisfactory, the free-standing flexible PBEDTH films will still be promising in the areas of energies and sensors in the true sense.